Cultural and scientific aspects in magazine "Fjala" 1974-1991 - Kosovar BASHA (Celal Öney, 2021)
Through this paper, the author aims to shed some light on this important body for the cultural and scientific life of Kosovo. Having in mind that few scholars to date have addressed this topic, the author of this study fully analyzes the "Fjala" (‘The Word’) in terms of content and quality. Overall, the magazine "Fjala" through its articles in the field of literature, art, as well as history, sociology, etc., successfully introduced the Albanian culture and science of Kosovo. To complete the paper in question, we have used the synthesizing and descriptive method so that the historical context of this journal is as objectively analysed as possible.